Crescimento e caracterização do complexo ternário de 1,10 – Fenantrolina e Serina complexado com Cobre (II) para utilização como antitumoral - RAMOS, Marina Costa (2019)
Transition metal ions such as copper have been the subject of studies and have been gaining ground in the scientific field, aiming to develop new drugs with significant pharmacological properties to be used especially in cancer therapies. Cancer is a disease of different diagnoses that is difficult to treat due to the diversity and complexity of its tumors, alarming data are presented due to the number of deaths associated with this pathology. Therefore, this study aimed the 1,10-Phenantroline and Serine complexed with Copper (II) ternary crystal synthesis, as well as the study of the physico-chemical properties in view of their application in antitumor activity. The sample was synthetized by slow evaporation solvent method was used and the crystal was obtained after seven days. The crystal was characterized by X-ray Diffraction (XRD) with Rietveld refinement, Scanning Electron Microscopy (SEM), Energy Dispersion XRay Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR) ), Raman Spectroscopy, Thermogravimetric Analysis (TG), Differential Thermal Analysis (DTA), Magnetization, antitumor activity evaluation and Solubility Test. XRD measurements at room temperature, showed that the crystal have a triclinic structure, space group P1 and lattice parameters: a = 7.6358 (3) Å, b = 10.0523 (4) Å, c = 12.0204 (7) Å, and angles α = 97.43 (3) °, β = 106.84 (3) °, γ = 108.75 (3), containing 2 molecules for unit cell. The SEM and EDS analyzes showed interfacial defects on the crystalline surface and the elemental composition of the sample, respectively. The Raman and FTIR spectra confirmed the complexation of the Cu2+ ion with the organic molecules. From the thermoanalytical techniques the thermal stability of the crystal up to 60 ºC was verified. The XRD as a function of temperature (303 to 493 K) showed the phase transformation of the material from its hydrated to anhydrous form, forming the water outlet of the material. Using the Le Bail method for refinement of the structure determined that the material remained with structure triclinic P1. Raman spectroscopy with temperature variation (294 to 433 K) confirmed the phase transformation detected by XRD. Magnetization analysis revealed that the crystal is a material with paramagnetic properties. The antitumor activity of the crystalline system was confirmed by cytotoxic assays in HCT-116 tumor cell line with an IC50 = 2.14 µM higher than the cisplatin complex (IC50 = 8.3 µM). The crystal showed an aqueous solubility profile considered good when compared to drugs used to treat cancer, reaching 21.61 mg / mL in 180 minutes.